Planning for self-employment at the beginning of a market economy: evidence from individual data of East German workers - Michael Lechner; Friedhelm Pfeiffer (Zentrum für Europäische Wirtschaftsforschung (ZEW); ZBW – Leibniz Information Centre for Economics, 1992)
We investigate the plans of individual workers concerning future self-employment in the former German Democratic Republic (East Germany) shortly before the economic, monetary and social union in June/July 1990. Our data base is the Socio-Economic Panel (SOEP) East. We find that the desire to become an entrepreneur is basically determined by individual and household characteristics, including income and asset indicators, and not as much by the current job situation of the individual. Furthermore, we find evidence of barriers to entry which may come from capital market constraints and institutional restrictions. Due to the ordinal nature of the answers, we used the ordinal logit model for estimation. The corresponding stochastic assumptions are tested extensively using pseudo-Lagrange multiplier tests against omitted variables, non-linearity, asymmetry of distribution, and heteroscedasticity.
Keywords: 330; Selbstständige; DDR